Usage of the extract of Artemisia vulgaris in hexane in the in vitro control of Rhipicephalus microplus (Research, Society and Development, 2021)
Rhiphicephalus microplus infestations cause considerable losses in Brazilian cattle farming resulting in several damage as weight loss and low feed conversion, which may affect the production of meat and milk. The extract of plants is utilized as an alternative form to control ticks, since the indiscriminate use of acaricides is causing populations of even more resistant ticks. Therefore, in conformity to the above, the present work aimed to analyze the in vitro reproductive efficiency of actives extracted in apolar solvent (hexane) of the plant Artemisia vulgaris on the tick Rhipicephalus microplus. At first, to analyze the in vitro efficacy of A. vulgaris extracts, it was used teleogines from the colony of R. microplus from the Laboratory of Experimental Chemotherapy in Veterinary Parasitology of UFRRJ (LQEPV), which were divided into groups of 10 and submitted to the test of immersion in hexane at a concentration of 1250 ppm, as well as positive and negative control. The measurement of the percentage of hatchability, which was performed to calculate the Reproductive Efficiency of the Product, was done using variance analysis. In this way, despite the fact that there are few studies that prove the efficacy of A. vulgaris as a biocarpaticide, it could be concluded with the present study that when it was extracted in hexane it demonstrated a good efficiency in the in vitro control of R. microplus.